Analysis of Stock Prices and Transaction Volumes of BRIS Before and After the Ransomware Attack - Malik, Ahmad Dahlan; Khoirunnisa; Handono, Wahyu Agung; Hanesti, Elsi Mersilia (Sustainability and Social Impact, 2025)
Bank Syariah Indonesia (BSI) is currently the largest Islamic bank in Indonesia. However, BSI recently experienced disruptions in several services, including mobile banking, due to a ransomware attack that essentially locks access to data, thereby disrupting business operations. This phenomenon also led to a decline in BSI's stock, coded BRIS. The purpose of this study is to determine the differences in stock prices and transaction volumes before and after the ransomware attack. This research employs a quantitative method with a comparative research approach. The data sources for this study are secondary data obtained from the websites www.finance.yahoo.com and www.idx.co.id. The analysis techniques used include descriptive statistical analysis, normality tests, and hypothesis testing. The results of the hypothesis tests using the Paired Sample T-Test for stock prices and the Wilcoxon Signed Ranks Test for transaction volumes indicate significant differences in stock prices and transaction volumes before and after the ransomware attack that occurred in 2023.